Sosialisasi Hama Wereng pada Tanaman Padi di Desa Gedangkulut Kecamatan Cerme - Afifah Dinda Sofia; Dita Noer Novitasari; Muthiatur Rahmah; Nisa Hafi Idhoh Fitriana (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Rice is one of the important food crops for the people of Indonesia to meet the need for carbohydrates. This food ingredient contains 73 g of carbohydrates and 8 g of protein in every 100 g of material. As a major food crop, continuity of production is urgently needed so that the quality and quantity remains available. The obstacle often faced by farmers in efforts to increase rice production is the presence of plant-disturbing organisms (OPT). One type of plant-disturbing organism that attacks rice plants is the Wereng Pest, causing losses in quality and quantity. Brown planthoppers and green leafhoppers are groups of pests that can cause rice plants to die or reduce production to the detriment of farmers. The purpose of this research is to conduct outreach to farmers regarding the dangers and what can be done so as not to be exposed to Wereng Pests. This activity was held on June 19 2023 in Gedangkulut Village, Cerme District, Gresik Regency.